Effects of aryl organophosphate ester exposure on female reproductive health by 571 infertile women in vitro fertilization from January 2018 January 2021 - Shuyi ZHANG; Yuanfen WANG; Fumei GAO; Min FU; Xiaohua ZHANG; Huan SHEN (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo analyze the effects of aryl organophosphate esters (aryl-OPEs) on female reproductive health. MethodsUrine samples from 571 women with infertility who sought in vitro fertilization-embryo transfer treatment at the Reproductive Center of Peking University People's Hospital from January 2018 to January 2021 were tested for concentrations of four aryl-OPE metabolites: diphenyl phosphate (DPHP), 4-hydroxyphenyl diphenyl phosphate (4-OH-TPHP), 2-ethyl-5-hydroxyhexyl diphenyl phosphate (5-OH-EHDPP), and 4-(hydroxymethyl)phenyl di-p-tolyl phosphate (4-OH-MDTP). Continuous independent variable data were converted into categorical variables, divided into four levels (Q1, Q2, Q3, Q4) using the 25th, 50th, and 75th percentiles as cut-off points. After reassigning values to the independent variables in each group, they were incorporated into the regression model as continuous variables for trend testing. Using multivariable linear mixed models, the correlations between aryl-OPE metabolite concentrations and reproductive hormones [estradiol (E2), progesterone (P), testosterone (T), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and prolactin (PRL)] and infertility causes were assessed by adjusting for relevant covariates (age, BMI, smoking status, education level, infertility reason, and primary infertility diagnosis). ResultsThe detection rates of the four aryl-OPE metabolites were all > 80%. The results of the multivariable linear regression model showed that the concentrations of 4-OH-MDTP and 5-OH-EHDPP in urine were associated with decreased E2 levels (P < 0.05). The E2 level in the 4-OH-MDTP Q3 group was significantly lower by 20.59% compared to the Q1 group, and in the 5-OH-EHDPP Q4 group, it decreased by 34.52% compared to the Q1 group. The exposure concentrations of 4-OH-TPHP and DPHP showed a significant positive correlation with progesterone levels (P < 0.05). The progesterone level in the 4-OH-TPHP Q3 group was significantly increased by 42.42% compared to the Q1 group, and in the DPHP Q4 group, it was significantly increased by 32.85% compared to the Q1 group. In the analysis of infertility causes, the concentrations of 4-OH-TPHP and 4-OH-MDTP in patients with polycystic ovary syndrome (PCOS) and endometriosis were significantly higher than those in women undergoing in vitro fertilization due to male factors. Moreover, the risk of PCOS and endometriosis increased in the 4-OH-TPHP and 4-OH-MDTP Q2-Q4 groups compared to the Q1 group. ConclusionAryl-OPEs can interfere with estrogen and progesterone levels in women. The parent compounds and metabolites may be associated with the occurrence of PCOS and endometriosis and could be one of the causes of infertility.